Perubahan Nilai Keluarga dalam Pengembangan Usaha Kuliner Soto Kadipiro di Yogyakarta - Ahmad Izudin (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
There are in views that the families were the lack of relevance within the independent process to social care program. It has triggered to debating issue on the role of family within developing of micro and small enterprises. To add more on such issues, the study presents to examine about changing of family values and its implication to developing of culinary enterprises in Yogyakarta. Soto Kadipiro as the culinary business was chosen to conduct research, in which is as a case study to seek about the role of pioneering culinary enterprise with qualitative methods. Observed, desk-reviewed and interviewed applied following the data collection, and the researcher used historical approach to gain understanding of phenomena. The study finds that pioneering, developing, and maintaining of culinary enterprise has only carried out by the internal family of Soto Kadipiro. This fact reveals that changing role of family can be seen as an alternative way within developing of micro and small enterprises to gain of economic growth and increasing prosperity. It implicates to look at into a part of changing gender relations, educations, internal of family, and social class. As such, the social welfare should be employed with seeking the changing of internal families for the gaining roadmap of welfare provision in the future.